Aplikasi E-News Untuk Informasi Berita Teknologi Komputer Dengan Pendekatan Classic Life Cycle Model - Susafaati Susafaati; Nunung Hidayatun; Hidayanti Murtina (Jurnal Teknik Komputer AMIK BSI, 2022)
Current technology has undergone rapid development especially komputer technology, so it has an impact in increasing the effectiveness and efficient in work. As well as information and communication technology especially the internet that encourages the dissemination of an information or news that is wider and the technology used to convey the needs of the community will be news that is easily accessible and up to date news portal website using IE. Despite its advanced technology, not a few among the public who still do not know in operating the komputer. Therefore, the authors are interested in to make a website portal news komputer technology. The purpose of this research was able to build a web that can render the information source for the public to better recognize and know how to operate the komputer correctly. And methods used in the design of the web include the observation and study of the literature, analysis, design, testing (testing) as well as modeling technique which is described with the Unifield Modeling Language (UML). The expected results are can do spread the news or information about komputer technology through the medium of the internet.